Novel Approaches to Allergen Immunotherapy for Respiratory Allergies - Mongkol Lao-Araya (Pharmaceuticals)
Allergen immunotherapy (AIT) remains the cornerstone for managing respiratory allergies, offering long-term symptom relief, disease modification, and prevention of disease progression. While novel approaches like intralymphatic and epicutaneous immunotherapy and the combination of allergens with adjuvants show promise, traditional methods remain effective and safe. Hypoallergenic T-cell peptide vaccines and recombinant allergens require further research to confirm their clinical benefits. Passive immunotherapy, while demonstrating effectiveness in specific cases, needs exploration of its long-term efficacy and broader applicability. Combining AIT with biologics may enhance safety and treatment outcomes. Despite emerging innovations, allergen-specific immunotherapy with natural allergen extracts remains the primary disease-modifying treatment, offering long-term symptom relief and prevention of disease progression. Continued research is essential to refine and optimize allergen immunotherapy strategies, providing patients with more effective and personalized treatment options.